Indonesian Traditional Games: a Way to Implant Character Education on Children and Preserve Indonesian Local Wisdom - Niswatin Nurul Hidayati (ISTAWA, 2020)
Indonesia is a country that is rich in culture, one of which is reflected in a variety of traditional games. Traditional games are inherited from ancestors which are not only used for entertainment, but contain values and messages contained in them. At the end of this traditional game is not widely played or even unknown to children. This is because of the widespread use of gadgets and online games that have been played from an early age. In this short article, the author describes several traditional Indonesian games with the values contained therein. The author randomly chooses several traditional games to then describe them. This is done with the hope of promoting the return of traditional games for children, because in the game it is one way to instill the value of character education in children. In addition, by promoting traditional Indonesian games, Indonesia will also maintain local wisdom.Indonesia adalah negara yang kaya akan budaya, salah satunya tercermin dengan berbagai macam permainan tradisional yang dimiliki. Permainan tradisional adalah merupakan warisan dari leluhur yang tidak hanya digunakan untuk hiburan, namun mengandung nilai dan pesan yang terkandung di dalamnya. Akhir kahir ini permainan tradisional tidak banyak dimainkan atau bahkan tidak dikenal oleh anak anak. Hal ini karena maraknya penggunaan gadget dan online games yang telah dimainkan mulai usia dini. Dalam tulisan singkat ini, penulis mendeskripsikan beberapa permainan tradisional Indonesia dengan nilai nilai yang terkandung di dalamnya. Penulis memilih beberapa permainan tradisional secara acak untuk kemudian mendeskripsikannya. Hal ini dilakukan dengan harapan digalakkannya kemabali permainan tradisional untuk anak, karena dalam permainan tersebut menjadi salah satu cara untuk menanamkan nilai nilai Pendidikan karakter pada anak. Di samping itu, dengan digalakkannya permainan tradisional Indonesia, juga akan menjaga local wisdom yang dimiliki Indonesia